The impact of achievement goals on cheating in sport. (March 2018) - Ring, Christopher; Kavussanu, Maria
Abstract: Objective: The purpose of this research was to investigate the impact of achievement goals on cheating in sport. Designs: We used cross-sectional (Study 1, Study 3) and experimental (Study 2) designs. Method: In Study 1 ( N  = 144) we measured athletes' dispositional goal orientation and attitudes towards cheating. In Study 2 ( N  = 125) we manipulated goal involvement and measured cheating in hypothetical situations. In Study 3 ( N  = 60) we examined the link between goal orientations and cheating in running races. Results: In Study 1, acceptance of cheating was positively related to ego orientation and negatively related to task orientation. In Study 2, cheating in hypothetical sport situations was more likely for ego-involved and task-involved than control participants. In Study 3, athletes who illegitimately improved their race times to enhance their chances of winning scored higher in ego orientation and lower in task orientation than those who did not illegitimately improve their race times. Conclusions: The findings provide evidence for the motivation-cheating relationship thereby supporting predictions of achievement goal theory in the context of sport, particularly with respect to ego goals. Our findings suggest that interventions aimed to promote fair play in sport could focus on influencing the goals of the athletes. Highlights: The effect of achievement goals on cheating was examined. Ego orientation was positively related to acceptance of cheating (Study 1). Ego involvement increased cheating likelihood in hypothetical scenarios (Study 2). Ego orientation was higher among cheats than non-cheats (Study 3). Risk for cheating among athletes with win at any cost motivation.